Medication Errors and Blood Pressure Control Among Patients Managed for Hypertension in Public Ambulatory Care Clinics in Botswana. Issue 2 (21st January 2020) - Gala, Pooja; Moshokgo, Veronica; Seth, Bhavna; Ramasuana, Kegomoditswe; Kazadi, Emmanuel; M'buse, Rudy; Pharithi, Solomon; Gobotsamang, Kabelo; Szymanowski, Paige; Kerobale, Ruth Olyn; Balekile, Kelennetse; Tshimbalanga, Jacques; et al.
Abstract : Background: The prevalence of hypertension in low‐ and middle‐income countries is rapidly increasing, with most cases undiagnosed and many poorly controlled among those diagnosed. Medication reconciliation studies from high‐income countries have demonstrated a high occurrence of antihypertensive medication errors and a strong association between medication errors and inadequate blood pressure control, but data from low‐ and middle‐income countries are lacking. Methods and Results: We conducted a cross‐sectional study from April to October 2018 of adult patients on pharmacologic management for known hypertension at 7 public health facilities in Kweneng East District, Botswana. Our aims included to evaluate the frequency of uncontrolled hypertension, the frequency and type of medication errors causing discrepancies between patient‐reported and prescribed antihypertensive medications, and the association between medication errors and uncontrolled hypertension. Descriptive analyses and multivariable logistic regression were used. The prevalence of uncontrolled hypertension was 55% among 280 enrolled adult patients, and 95 (34%) had ≥1 medication error. The most common errors included patients taking medications incorrectly (11.1%; 31/280), patients omitting medications (7.9%; 22/280), and unfilled prescriptions caused by pharmacy stock outs (7.5%%; 21/280). Uncontrolled hypertension was significantly associated with having ≥1 medication error compared with no errors (adjusted odds ratio, 3.26; 95% CI, 1.75–6.06; P <0.001). Conclusions: Medication errors are strongly associated with poor blood pressure control in this setting. Further research is warranted to assess whether medication reconciliation and other low‐cost interventions addressing root causes of medication errors can improve the control of hypertension and other chronic conditions in low‐ and middle‐income countries.